Methods of Cancer Diagnosis, Therapy and Prognosis Breast Carcinoma - Hayat, M. A. (Methods of Cancer Diagnosis, Therapy and Prognosis, 2008)
This is the first book that discusses subjects of diagnosis, therapy, therapy assessment, and prognosis of breast cancer in one single volume. Cancer killed 6.7 million people around the world in 2002 and this figure is expected to rise to 10.1 million in 2020. Approximately, 189,510 new cases of breast cancer were reported in 2007 in the United States, and 40,910 died in the same year. Focusing on Breast Carcinoma, this first volume in the series Methods of Cancer Diagnosis, Therapy and Prognosis brings together 56 leading scientists from around the world to deliver a comprehensive treatise on all aspects of breast cancer, including diagnosis, treatments and prognosis. Scientists and clinicians have contributed state of the art chapters on their respective areas of expertise providing the reader a whole field view of breast cancer management. This fully illustrated volume: * Presents a constructive evaluation of commonly used methods for elucidating primary and secondary cancer initiation, progression, relapse, and metastasis. * Highlights methods of breast cancer diagnosis and treatment assessment including various imaging modalities such as ultrasound, computed tomography, magnetic resonance imaging, immunohistochemistry and histochemistry. * Discusses detailed therapeutic protocols, including both their benefits and side-effects. * Discusses examples of breast cancer treatments includingchemotherapy, radiation, chemoradiation, surgery, hormonal - and immunotherapy * Details the molecular processes that lead to the development and proliferation of cancer cells * Includes recent major advances in cancer diagnosis and therapy assessment Professor Hayat has summarized the problems associated with the complexities of research publications and has been successful in editinga must-read volume for oncologists, cancer researchers, medical teachers and students of cancer biology.